Determinants of poverty : evidence from Europe countries (2006-2015) / Nor Farwizah Amirun Ajit - Amirun Ajit, Nor Farwizah (2020)
The purpose of this study was to examine the determinants of poverty in Europe countries. The dependent variable of this study is poverty gap while independent variable are gross domestic product, income inequality, population growth and unemployment. The type of data used in this study is panel data. The sample pf study consists of 6 Europe countries and data collected cover the period from 2006 until 2015. This current study employs a Panel Regression Fixed Effect Model in order to study the determinants of poverty in Europe countries. The result of this study showed that income inequality has positively significant relationship between poverty. Next, unemployment is positive but insignificant relationship between poverty. In addition, gross domestic product have negatively significant relationship between poverty.